ODONTOCHILUS UNIFLORUS (BLUME) H.Ǣ. PEDERSEN & ORMEROD: A NEW ADDITION OF THE JEWEL ORCHIDS FOR FLORA OF JAVA - Lina Susanti Juswara (Research Center for Biology-Indonesian Institute of Sciences, 2020)
Odontochilus uniflorus (Blume) H.Ǣ. Pedersen &Ormerod, is a new addition to Flora of Java based on three specimen collected from Mt. Halimun-Salak National Parks. This species was previously known only from Thailand, Malaysia, and Sumatra. Hence, this new finding expands the range of distribution of the species of O. uniflorus as well as adding information for orchids of Java. Identification key of the species of Odontochilus in Java is also presented in this paper.